2018
DOI: 10.1007/s00702-018-1862-8
|View full text |Cite
|
Sign up to set email alerts
|

Flavor perception and the risk of malnutrition in patients with Parkinson’s disease

Abstract: Flavor perception involves both olfactory and gustatory function. In patients with Parkinson’s disease (PD), hyposmia is a frequent finding, as well as an increased risk of malnutrition. We performed a pilot study to investigate the relationship between flavor perception and risk of malnutrition in PD patients. 63 PD patients participated to perform an olfactory (Sniffin’ Sticks) and gustatory (Taste Strips) task, and a questionnaire to establish nutritional risk (MUST), which includes BMI measurements. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
2
16
0
4
Order By: Relevance
“…4 Anosmia was associated herein with lower food intake although it was not associated with persistent malnutrition at D30. While alteration of flavour perception may contribute to weight loss in other diseases, 5 patients with olfactory disorders in the current study had less frequently subjective functional loss or severe disability at D30. The protective effect of anosmia has been reported in other studies showing that olfactory disorders less frequently necessitated oxygen therapy 32 and was associated with milder forms in patients who did not require hospitalisation.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…4 Anosmia was associated herein with lower food intake although it was not associated with persistent malnutrition at D30. While alteration of flavour perception may contribute to weight loss in other diseases, 5 patients with olfactory disorders in the current study had less frequently subjective functional loss or severe disability at D30. The protective effect of anosmia has been reported in other studies showing that olfactory disorders less frequently necessitated oxygen therapy 32 and was associated with milder forms in patients who did not require hospitalisation.…”
Section: Discussionmentioning
confidence: 48%
“…Olfactory and gustatory dysfunction are common symptoms in patients with COVID-19 4 and may contribute to weight loss in other diseases, thereby increasing the risk of malnutrition. 5 One study, conducted in Wuhan, China, showed that the prevalence of malnutrition based only on the Mini Nutritional Assessment in 182 elderly patients with COVID-19 was high (52.7%), especially for those with diabetes mellitus, low calf circumference or low albumin. 6 Persons with diagnosed COVID-19 are also likely to exhibit decreased muscle function resulting in secondary sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed a negative association between the severity of motor impairment and total fat mass in patients with PD ( 7 ). Another study showed that malnutrition in PD patients can cause olfactory and gustatory dysfunction ( 9 ). Nutritional risk screening plays an increasingly important role in PD.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, inactivity and bed rest accelerate muscle catabolism. Olfactory and gustatory dysfunction are common symptoms in patients with COVID-19 [2] and may contribute to weight loss in other diseases, thereby increasing the risk of malnutrition [3]. Malnutrition can be prevented or contained by prompt nutritional support [6].…”
Section: Introductionmentioning
confidence: 99%